Pengaruh Lingkungan Kerja dan Insentif Terhadap Kepuasan Kerja Guru Di SMA Negeri 6 Batang Hari - Redo Prayitno (Pusat Riset dan Inovasi Nasional, 2024)
Redo Prayitno. 2023. The Influence of the Work Environment and Incentives on Teacher Job Satisfaction at SMA Negeri 6 Batang Hari. Thesis, Islamic Education Management, Batang Hari Nusantara Islamic Institute. Based on the author's initial grand tour, there are various factors that influence teacher job satisfaction at SMA Negeri 6 Batang Hari. This research aims to determine the influence of the work environment and incentives on teacher job satisfaction at SMA Negeri 6 Batang Hari. This research is quantitative research with a type of approach. The population of this research is the number of all teachers who teach at SMA Negeri 6 Batang Hari. The data analysis used was multiple regression analysis and the data was processed with the help of the SPSS Version 20.0 program. The research results show that the work environment has a significant effect on job satisfaction with tcount>ttable (5.541>1.693). This shows Ha is rejected and H0 is accepted. Incentives have a significant effect on job satisfaction with the value obtained tcount>ttable (3.491>1.693). This shows that Ha is rejected and H0 is accepted. This means that there is a partial influence between the Work Environment and Incentives on job satisfaction. By looking at the results of the coefficient of determination (r square) of 0.961, which means that the Work Environment and Incentive variables are able to increase job satisfaction decisions by 96.1% and 0.039 or 3.9% is the remaining variable (residue) which is influenced by other variables.